Analisis Hukum Ekonomi Terhadap Kebijakan Angkutan Umum di Kota Medan; Perspektif Al-Maslahah - Hasibuan, Irfan Effendi; Zulham, Zulham (Al - Muamalat: Jurnal Hukum dan Ekonomi Syariah, 2025)
The purpose of this research is to analyze public transportation policies in Medan City from the perspective of economic law using the principle of al-maslahah to evaluate the extent to which these policies prioritize public welfare, particularly in terms of passenger safety, comfort, and security. This study aims to provide policy recommendations that are more effective in addressing the existing issues in Medan's public transportation system. This article falls under qualitative field research. The methodology employed is normative legal study, presented in a descriptive-analytical narrative. The findings reveal that current public transportation policies in Medan City do not fully adhere to the principle of al-maslahah, as there is still disorder in the operation of public transportation that potentially harms the public. The lack of oversight, inadequate facilities, and neglect of passenger safety and comfort standards have resulted in public losses and a decline in trust toward public transportation.